The effect of Er3+ concentration on the kinetics of multiband upconversion in NaYF4:Yb/Er microcrystals - Huang, Hanchang; Zhong, Yanyi; Li, Mingchen; Cui, Wenda; Yu, Tongcheng; Zhao, Guomin; Xing, Zhongyang; Guo, Chuan; Han, Kai (Frontiers in Chemistry, 2023)
In Yb-Er co-doped upconversion (UC) nanomaterials, upconversion luminescence (UCL) can be modulated to generate multiband UCL emissions by changing the concentration of activator Er3+. Nonetheless, the effect of the Er3+ concentrations on the kinetics of these emissions is still unknown. We here study the single β-NaYF4:Yb3+/Er3+ microcrystal (MC) doped with different Er3+ concentrations by nanosecond time-resolved spectroscopy. Interestingly, different Er3+ doping concentrations exhibit different UCL emission bands and UCL response rates. At low Er3+ doping concentrations (1 mol%), multiband emission in β-NaYF4:Yb3+/Er3+ (20/1 mol%) MCs could not be observed and the response rate of UCL was slow (5–10 μs) in β-NaYF4:Yb3+/Er3+. Increasing the Er3+ doping concentration to 10 mol% can shorten the distance between Yb3+ ions and Er3+ ions, which promotes the energy transfer between them. β-NaYF4:Yb3+/Er3+ (20/10 mol%) can achieve obvious multiband UCL and a quick response rate (0.3 µs). However, a further increase in the Er doping concentration (80 mol%) makes MCs limited by the CR process and cannot achieve the four-photon UC process (4F5/2 → 2K13/2 and 2H9/2 → 2D5/2). Therefore, the result shows that changing the Er3+ doping concentration could control the energy flow between the different energy levels in Er3+, which could affect the response time and UCL emission of the Yb/Er doped rare earth materials. Our work can facilitate the development of fast-response optoelectronics, optical-sensing, and display industries.